Sodium-glucose cotransporter–2 (SGLT2) inhibitors and the reporting of falls and fractures: an european pharmacovigilance analysis - Mascolo, Annamaria; Rafaniello, Concetta; di Mauro, Gabriella; Ruggiero, Donatella; Campitiello, Maria Rosaria; Donniacuo, Maria; Berrino, Pasquale Maria; Rossi, Francesco; Paolisso, Giuseppe; Capuano, Annalisa (Frontiers in Pharmacology, 2023)
Background: The risk of falls and bone fractures with sodium-glucose co-transporter-2 (SGLT2) inhibitors has been characterized by conflicting evidence. Therefore, we decided to investigate the reporting probability of falls and fractures by comparing SGLT2 inhibitors with DPP4 inhibitors. Methods A retrospective, pharmacovigilance study of the European database of Individual Case Safety Reports (ICSRs) was conducted. Disproportionality analyses (Reporting Odds Ratio, ROR) were conducted to compare the reporting probability of falls or fracture between treatments. Results A total of 507 ICSRs reporting at least one fall or fracture with SGLT2 inhibitors were identified. The most reported SGLT2 inhibitor was canagliflozin (N = 188; 36.9%), followed by empagliflozin (N = 176; 34.5%), and dapagliflozin (N = 143; 28.0%). A total of 653 events related to fall or bone fracture were reported. Fall was the most reported event (N = 333; 51.0%). Among fractures (N = 320; 49.0%), the most reported were foot fractures (N = 40; 6.1%) and hip fractures (N = 32; 4.9%). SGLT2 inhibitors were associated with a lower reporting probability of fall than DPP4 inhibitors (ROR, 0.66; 95%CI, 0.57-0.78). The lower reporting probability of fall was also observed when the single SGLT2 inhibitor was compared to DPP4 inhibitors: dapagliflozin (ROR, 0.67; 95%CI, 0.53-0.83), canagliflozin (ROR, 0.56; 95%CI, 0.45-0.70), and empagliflozin (ROR, 0.77; 95%CI, 0.63-0.94). For fractures, canagliflozin showed a slightly significant increased reporting when compared with DPP4 inhibitors (not confirmed in the sensitivity analysis), whereas all other comparison showed no statistically significant difference. Conclusion SGLT2 inhibitors were associated with a lower reporting probability of fall than DPP4 inhibitors, in accordance with the reassuring evidence about the safety profile of these drugs. Future researches will help to confirm their long-term safety profile.